Knockdown of EIF4G1 in NSCLC induces CXCL8 secretion - He, Ziyang; Li, Fangyi; Zhang, Xinyi; Gao, Dacheng; Zhang, Zhiwen; Xu, Rui; Cao, Xingguo; Shan, Qiyuan; Ren, Zhen; Liu, Yali; Xu, Zengguang (Frontiers in Pharmacology, 2024)
Non-small cell lung cancer (NSCLC) is the most common type of lung tumor; however, we lack effective early detection indicators and therapeutic targets. Eukaryotic translation initiation factor 4 gamma 1 (EIF4G1) is vital to initiate protein synthesis, acting as a scaffolding protein for the eukaryotic protein translation initiation factor complex, EIF4F, which regulates protein synthesis together with EIF4A, EIF4E, and other translation initiation factors. However, EIF4G1's function in NSCLC cancer is unclear. Herein, transcriptome sequencing showed that knockdown of EIF4G1 in H1299 NSCLC cells upregulated the expression of various inflammation-related factors.Inflammatory cytokines were also significantly overexpressed in NSCLC tumor tissues, among which CXCL8 (encoding C-X-C motif chemokine ligand 8) showed the most significant changes in both in the transcriptome sequencing data and tumor tissues. We revealed that EIF4G1 regulates the protein level of TNF receptor superfamily member 10a (TNFRSF10A) resulting in activation of the mitogen activated protein kinase (MAPK) and nuclear factor kappa B (NFκB) pathways, which induces CXCL8 secretion, leading to targeted chemotaxis of immune cells. We verified that H1299 cells with EIF4G1 knockdown showed increased chemotaxis compared with the control group and promoted increased chemotaxis of macrophages. These data suggested that EIF4G1 is an important molecule in the inflammatory response of cancer tissues in NSCLC.